The effect of Islamic music listening on the psychological well-being of university students in Malaysia - Awaluddin, Nursyafini; Mohamad Shariff, Nurasikin; Wan Mamat, Wan Hasliza; Ahmad, Azmir (Universiti Putra Malaysia, 2025)
Introduction: Music therapy that aligns with Islamic values is endorsed and permitted by Imam Syafi’e and scholars such as Al-Razi, Farabi, and Ibn Sina. Accordingly, Malaysian university students aged 20 and above, who exhibit higher depression and anxiety scores, may seek solace in music. The current study examined the psychological well-being of Malaysian public university students before, immediately after, and one month following daily Islamic music therapy. Materials and Methods: A quasi-experimental repeated measures study was conducted on 46 undergraduate students from a public university. Participants, screened for psychological distress, engaged in daily 15-minute sessions of Islamic music for six weeks. Their psychological well-being was assessed using the DASS-21 questionnaire at three intervals: before the intervention, immediately after, and one month later. One-way repeated measures ANOVA tested the hypothesis. Results: The total DASS-21 score, including depression, anxiety, and stress categories, significantly decreased post-intervention and remained low after one month without further intervention (p<0.05). Participants did not experience an increase in psychological distress during the follow-up period. Conclusion: Islamic music significantly reduced psychological distress among Malaysian students, with sustained effects observed one month later. Thus, daily exposure contributes to coping and relaxation. The single-group design controlled for individual differences offers clear insights into Islamic music’s impact. This study suggests nurses use Islamic music as a culturally sensitive intervention to improve patients’ psychological, mental health, and well-being. Future studies should explore long-term effects and include larger, randomised controlled trials to validate findings and examine variables such as spiritual well-being and religiosity.